A Systematic Literature Review on the Role of Qur’anic Memorization in Enhancing Arabic Language Acquisition - Rachmanda Fikri; Talqis Nurdianto (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study aims to examine the role of Qur'an memorization (tahfizh) in improving Arabic language skills and learning motivation among Indonesian students through the Systematic Literature Review (SLR) method. The increasing number of tahfizh educational institutions in Indonesia necessitates a critical evaluation of whether memorization activities actually contribute to Arabic language acquisition. Data were collected from scientific articles published between 2020-2024 in the Google Scholar, Garuda, and SINTA databases, then analyzed using thematic analysis. The literature synthesis results indicate that tahfizh plays a positive role in strengthening phonological aspects, reading fluency, and mastery of Arabic vocabulary. Tahfizh also has the potential to increase learning motivation by strengthening religious orientation, self-regulation, and persistence. However, the effect of tahfizh on grammatical skills and language productivity depends on intermediary factors such as understanding verse meanings, muraja'ah intensity, and a supportive Arabic learning environment. These findings confirm that tahfizh does not automatically improve all aspects of Arabic without the support of language practice and habituation. The theoretical implication is the need for an integrated model between tahfizh programs and systematic Arabic language instruction.